E-Filing System and Individual Taxpayer Compliance - Irawan , Dicky (Business, Accounting and Management Journal, 2023)
The purpose of this study was to analyze the effect of e-filing system implementation on individual taxpayer compliance with tax education and internet literacy as a moderating variable in the case study at KPP Pratama Cibitung. This study's population are individual taxpayers registered as e-filing taxpayers at KPP Pratama Cibitung. The sample in this study was 100 respondents. The hypothesis test used in this research is simple linear regression analysis and moderated regression analysis. The results of this study indicate that the effect of e-filing system implementation affects individual taxpayer compliance, tax education cannot moderate the effect of e-filing system implementation to individual taxpayer compliance, and internet literacy cannot moderate the effect of e-filing system implementation to individual taxpayer compliance. This research implies that in an effort to improve individual taxpayer compliance, the Directorate General of Taxes needs to improve the e-filing system, by providing better guidance and technical support. Then, an evaluation of the tax education program also needs to be carried out to ensure its effectiveness, if there is no influence between the e-filing system and taxpayer compliance, then the strategy for delivering educational material needs to be changed. Finally, taxpayers need to increase their understanding and skills in using the e-filing system and optimize the use of the internet as a source of tax information.